Interactive Marketing Strategies in Sustainable Fashion- An Analysis of Fabric Recycling and Upcycling Practices - Veronika Ita Karina Tarigan; Christina, Christina; Caroline Fransiska; Maria Magdalena Naomi Utami; Ayoedia Gita Citrayomie (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The fashion industry significantly contributes to the global economy but is also one of the largest sources of environmental degradation due to high water consumption, textile waste, and carbon emissions. In Indonesia, textile waste has become a major environmental concern, particularly in West Java. As a response, sustainable fashion has emerged as an alternative approach that emphasizes environmentally responsible production and consumption. This study aims to analyze the interactive marketing strategies implemented by the Sejauh Mata Memandang X Mulih collaboration in promoting sustainable fashion through fabric recycling and upcycling practices. Using a descriptive qualitative method within a constructivist paradigm and guided by the Integrated Marketing Communication (IMC) framework, data were collected through non-participant observation, structured interviews, and documentation. The findings reveal that interactive initiatives such as the “Kembali Baik” repair workshop, exhibitions, and storytelling effectively enhance consumer engagement, strengthen brand relationships, and increase environmental awareness. The collaboration successfully integrates online and offline communication channels to deliver consistent sustainability messages, positioning interactive marketing as both a promotional and educational tool in the sustainable fashion industry.